2013
DOI: 10.1186/1749-7922-8-58
|View full text |Cite
|
Sign up to set email alerts
|

Bariatric emergencies: current evidence and strategies of management

Abstract: BackgroundThe demand for bariatric surgery is increasing and the postoperative complications are seen more frequently. The aim of this paper is to review the current outcomes of bariatric surgery emergencies and to formulate a pathway of safe management.MethodsThe PubMed and Google search for English literatures relevant to emergencies of bariatric surgery was made, 6358 articles were found and 90 papers were selected based on relevance, power of the study, recent papers and laparoscopic workload. The pooled d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 82 publications
(85 reference statements)
0
6
0
Order By: Relevance
“…ROBSON et al (11) demonstrated that introduction of a subspecialised upper and lower gastrointestinal emergency surgical service was associated with a significant decrease in mortality in patients undergoing surgery for peptic ulcer perforation (10.4% vs. 20.3% ; p = 0.02). Recent guidelines proposed for management of bariatric emergencies stress the importance of early involvement of bariatric specialists (12). Our study extends further the domain over which specialist UGI surgeons can be expected to have better outcomes, as our population includes malignant upper gastro intestinal emergencies as well as benign.…”
Section: Discussionmentioning
confidence: 84%
“…ROBSON et al (11) demonstrated that introduction of a subspecialised upper and lower gastrointestinal emergency surgical service was associated with a significant decrease in mortality in patients undergoing surgery for peptic ulcer perforation (10.4% vs. 20.3% ; p = 0.02). Recent guidelines proposed for management of bariatric emergencies stress the importance of early involvement of bariatric specialists (12). Our study extends further the domain over which specialist UGI surgeons can be expected to have better outcomes, as our population includes malignant upper gastro intestinal emergencies as well as benign.…”
Section: Discussionmentioning
confidence: 84%
“…A leak may be the most feared complication when observing a peri-operative Amylase rise, since in two thirds of cases it may lead to sepsis and even to patient's death [18,41], and hence it may be critical to diagnose this complication and treat accordingly. This complication is contributed especially to a long staple line and high intraluminal pressure, and also to ischemia, hematoma formation, and staple mis ring.…”
Section: Discussionmentioning
confidence: 99%
“…Post-operative suspicion may be proceeding using abdominal CT, with or without a chest CT, or reexploration [42][43][44][45][46][47][48]. Despite gathering information about factors that are associated with an increased risk of a leak, and different ways to reduce this risk that have been offered, due to the heterogeneity of the studies and small statistical power there are still no recommendations of ways to prevent leaks [18,42,43,49].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Also, despite this radical intervention on the digestive system, some patients who underwent this surgery failed to lose weight [ 24 ] or regained weight lost shortly after the operation [ 25 ]. These patients may be subjected, therefore, to the revisional bariatric surgery that increases the risk of postoperative complications [ 26 , 27 ] and mortality [ 28 ]. Other patients with excessive weight, in turn, cannot be qualified for weight-loss operations because of medical contraindications or simply because of their reluctance to take on the risk of surgery.…”
Section: Introductionmentioning
confidence: 99%